Quality of Work Life of Public School Nurses in the Philippines - Macairan, Kaila Mae L.; Oducado, Ryan Michael F; Minsalan, Mika E; Recodo, Risa G.; Abellar, Gio Franco D. (Department of Nursing, Faculty of Medicine, Diponegoro University, 2019)
Background: School nurses play a crucial role in the provision of comprehensive health services to the school population. A balanced quality of work life (QWL) with favorable conditions that support and uphold employee satisfaction is imperative for school nurses to maximize their provision of care for their clientele. Among the many nursing specialties, research among school nurses is not given much attention.Purpose: This study aimed to determine the QWL of public school nurses in the Philippines.Methods: This study utilized a descriptive correlational research design with 57 public school nurses as study participants. Self-reported data were gathered utilizing Waltonâ€™s QWL scale. Data were analyzed using the Mann-Whitney U test, Kruskal-Wallis test, and Spearmanâ€“rank correlation coefficient.Â Results: Results indicated that public school nurses had high QWL (M=4.16). Among the eight subscales, opportunities at work (M=4.04) and social integration at work (M=4.03) had the lowest mean scores. There were no significant differences in the QWL according to sex (p=0.929), marital status (p=0.326), educational attainment (p=0.391) and length of work experience (p=0.059), while there was a significant relationship between age (p=0.005) and QWL of public school nurses.Conclusion: Public school nurses generally have a high QWL. Nevertheless, to further improve their QWL, it is recommended that public school nurses must be provided with more chances for continuous professional growth and opportunities for better social integration.